EXPLORING THE INPUT OF COMPETENCE ASSESSMENT TO GOAL-SETTING IN VARIOUS TYPES OF ORGANIZATIONS - Butkēviča, Anete; Zandbergs, Uldis; Namsone, Dace; Briķe, Signe (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of the present research is to investigate the existing practices of linking competence assessment to organizational goal-setting in various organisations in Latvia. The importance of linking employee competences to goal-setting within organizations has been established in scientific literature. Nevertheless, there is evidence gathered in this interdisciplinary research that existing methods of competence assessment used by various organizations in Latvia do not translate well into organizational goal-setting. The research is based on information gathered from semi-structured interviews with representatives of managerial positions in private and public, including educational service organizations (26 in total). Additionally, publicly available development plans are analysed. Empirical data are analysed according to a conceptual framework of criteria impacting the goal-setting process. Three subsets of criteria are used that guided interview question formulation and interview data analysis: formulation of a goal; employee’s ability to reach the assigned goal; employee’s self-assessment on his/her ability to reach the assigned goal. Analysis of the results indicate that when setting goals and assessing employee competences in relation to those goals, management decisions are greatly guided by subjective approaches. Such identified approaches in observed private and public service organizations indicate common risks that are discussed in this research.